Analyzing a Blockchain Application for the Educational Domain from the Perspective of a Software Ecosystem - Abreu, Antonio Welligton; Coutinho, Emanuel Ferreira; Bezerra, Wagner; Maia, Delano; Gomes, Alan Nascimento; Santos, Italo (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS); 2022: Anais do III Workshop sobre as Implicações da Computação na Sociedade, 2022)
Many educational institutions have the challenge of dealing with different data types. Some of this data is related to the issuance of student certificates. Software Ecosystem (SECO) refers to a collection of software products with some degree of symbiotic relationship.Blockchain can be used in different domains and its features of transparency and immutability are key concerns that make it an attractive technology. This article presents a discussion on an educational domain application from a SECO viewpoint that uses blockchain resources to treat the students' certificates from higher education institutions. Our findings were: a model of an educational application that uses blockchain and research opportunities related to SECO and blockchain for educational domain.